Mobile Fronthaul for next generation radio access networks - Mufutau, Akeem Olapade (2022)
The ever-increasing demand for better fixed and mobile broadband connectivity is evident and necessitates the search for new mobile networks with new requirements. Heterogeneous communication systems that can support various innovative wireless technologies, services and applications are envisioned for fifth-generation (5G) and upcoming sixth-generation (6G) networks. While there are several proposed architectures for radio access networks, the Cloud Radio Access Network (C-RAN), which has been widely considered as a promising and viable solution for the next generation network, has been criticized for its stringent mobile fronthaul (MFH) requirements due to the Common Public Radio Interface (CPRI) to achieve seamless connectivity. Considering the desired high capacities, optical fiber is an obvious transmission medium for building transparent links due to its low attenuation, insensitivity to electromagnetic interference, and enormous bandwidth. Nevertheless, the transmission of high-speed wireless channels over optical fibers poses a great challenge, especially when low latency and jitter are required. To overcome these challenges, optical transport technologies are used in this work. Moreover, considering the above requirements, possible transport solutions without CPRI for mobile fronthaul are investigated. Finally, to realize a flexible mobile fronthaul, a modified C-RAN prototype architecture is developed based on the extensive use of an open-source platform to demonstrate optical wireless convergence is demonstrated and promising results are presented in this thesis.